Estudo da produção e extração de compostos antioxidantes produzidos por Chlorella vulgaris - Pereira, Ana Cristina Lima (2018)
Microalgae have been shown to be a solution for obtaining antioxidant compounds. Antioxidants are compounds that slow the action of free radicals in the body. Among the compounds of interest, carotenoids are the most promising in this fight and have a high commercial value. The present work had as objective the selection of microalgae with capacity of antioxidant production, extraction and quantification of the same. The isolated strains were selected from the media for the production of antioxidant compounds, where the Chlorella vulgaris strain obtained the best result in relation to obtaining these compounds. Cultivation of the microalga strain Chlorella vulgaris was carried out in means of production with different compositions. After the cultivation of the strain an Experimental Design was carried out to determine the best production conditions for Chlorella vulgaris. Analysis of the extracted compounds was performed by UV spectrophotometry. Water and Dimethyl sulfoxide were used as solvents for the extraction of the samples and this was done together with the quantification thereof according to the method with 2, 2-diphenyl-1-picrylhydrazyl (DPPH). The results obtained were that the microalga Chlorella vulgaris presented the best potential for the production of carotenoids. The Carotenoid Mass (MC) values found comprised from 3.5 to 120.92 μg. In contrast, the existing Carotenoid Fraction (HR) values ranged from 0.58 to 37.17 μg. g-1 in the biomass of Chlorella vulgaris obtained. Biomass quantification was performed in relation to the Water Inhibition Index (IPH2O) and the Dimethyl sulfoxide Inhibition Index (IPDMSO) ranging from 15.69 to 60.22% and 13.75 to 24.96%, respectively. The best value for extraction of antioxidants was with IPH2O, which was 60.22%. The best conditions of production of these compounds in relation to the optimal ranges of the significant variables of the Design were at luminosity (X1) when it varied from 60 to 120 μmol. Photons m 2 s -1 and iron (X2) when it varied from 0.191 to 0.572 g / L. For MC, the optimum range was for the luminosity variable (X1) when it varied from 120 to 360 μmol. Photons. 2 s -1 e carbon (X3) when it ranged from 2.52 to 7.56 g / L. It is concluded that the microalga Chlorella vulgaris isolated from the effluent of the present anaerobic reactor was the one that obtained the best production of Total Carotenoids. It was able to extract antioxidants and the quantification of these compounds through the DPPH method. The value found in the quantification of the antioxidant activity of IPH2O was more efficient than with the solvent Dimethyl sulfoxide.